Thrombospondin Related Anonymous Protein Superfamily in Vector-Borne Apicomplexans: The Parasite’s Toolkit for Cell Invasion - Paoletta, Martina Soledad (2022)
Apicomplexan parasites transmitted by vectors, including Babesia spp. and Plasmodium spp., cause severe disease in both humans and animals. These parasites have a complex life cycle during which they migrate, invade, and replicate in contrasting hosts such as the mammal and the invertebrate vector. The interaction of parasites with the host cell is mediated by adhesive proteins which play a key role in the different cellular processes regarding successful progression of the life cycle. Thrombospondin related anonymous protein (TRAP) is a superfamily of adhesins that are involved in motility, invasion and egress of the parasite. These proteins are stored and released from apical organelles and have either one or two types of adhesive domains, namely thrombospondin type 1 repeat and von Willebrand factor type A, that upon secretion are located in the extracellular portion of the molecule. Proteins from the TRAP superfamily have been intensively studied in Plasmodium species and to a lesser extent in Babesia spp., where they have proven to be functionally relevant throughout the entire parasite’s journey both in the arthropod vector and in the mammalian host. In recent years new findings provided answers to the role of TRAP proteins and in some cases the function of these adhesins during the parasite’s life cycle was redefined. In this review we will discuss the current knowledge of the diverse roles of the TRAP superfamily in vector-borne parasites from Class Aconoidasida. We will focus on the varied approaches that allowed the understanding of protein function and the relevance of TRAP- superfamily throughout the entire parasite’s cell cycle.